2021
DOI: 10.1038/s42003-021-01978-6
|View full text |Cite
|
Sign up to set email alerts
|

A deimmunized and pharmacologically optimized Toll-like receptor 5 agonist for therapeutic applications

Abstract: The Toll-like receptor 5 (TLR5) agonist entolimod, a derivative of Salmonella flagellin, has therapeutic potential for several indications including radioprotection and cancer immunotherapy. However, in Phase 1 human studies, entolimod induced a rapid neutralizing immune response, presumably due to immune memory from prior exposure to flagellated enterobacteria. To enable multi-dose applications, we used structure-guided reengineering to develop a next-generation, substantially deimmunized entolimod variant, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…For example, the TLR2 is usually activated by the lipoproteins of Gram-positive bacteria, but it can also be activated by Pam3CSK4 [ 127 , 130 ]. Additionally, the CpG DNA is the natural agonist of TLR21, while the CpG DNA assemblies, synthetic single-stranded DNA, can also possess TLR21 enhancement activity [ 134 , 135 , 136 ].…”
Section: Vaccine Adjuvantsmentioning
confidence: 99%
“…For example, the TLR2 is usually activated by the lipoproteins of Gram-positive bacteria, but it can also be activated by Pam3CSK4 [ 127 , 130 ]. Additionally, the CpG DNA is the natural agonist of TLR21, while the CpG DNA assemblies, synthetic single-stranded DNA, can also possess TLR21 enhancement activity [ 134 , 135 , 136 ].…”
Section: Vaccine Adjuvantsmentioning
confidence: 99%
“…Results of this trial are yet to be available. While having the advantage of avoiding the dangerous inflammatory “cytokine storm” ( 276 ), Entolimod has a drawback that it can induce a rapid antibody neutralization ( 277 ),leading to its efficacy limitation. Pharmacological modification could be one solution to this problem.…”
Section: Recent Advances Of Tlr-targeted Tumor Therapiesmentioning
confidence: 99%
“…Pharmacological modification could be one solution to this problem. Mett et al ( 277 ) identified and eliminated the epitopes leading to Entolimod’s neutralizing immunogenicity and refined its structure to get GP532 as a new TLR5 agonist. GP532 reduced neutralizing antibody response while preserving pro-inflammatory capacity.…”
Section: Recent Advances Of Tlr-targeted Tumor Therapiesmentioning
confidence: 99%
“…Another study states that TLR-5 agonist mediated by flagellin later activates the transcription factors like NFκB and AP-1. These cause expression of several antiapoptotic, ROS scavenging genes, can limit the radiation damage in normal cells (29). This can be a new avenue for chemotherapy adjuvants.…”
Section: Figmentioning
confidence: 99%